Different effects on rat arterial pressure and heart rate when losartan is injected into the third or fourth ventricle - De-Luca, L. A. [UNESP]; Barbosa, S. P. [UNESP]; Menani, José Vanderlei [UNESP]; Camargo, L. A A [UNESP]; Saad, W. A. [UNESP]; Renzi, Antonio [UNESP] (My University, 1994)
Cardiovascular responses to central losartan (LOS), a non-peptide angiotensin II (ANG II) receptor antagonist, were investigated by comparing the effects of LOS injection into the 3rd and 4th cerebral ventricles (3rdV, 4thV) on mean arterial pressure (MAP) and heart rate (HR). Adult male Holtzman rats were used (N=6 animals per group). Average basal MAP and HR were 114±3 mmHg and 343±9 bpm (N=23), respectively. LOS (50, 100 or 200 nmol/2 μl) injected into the 3rdV induced pressor (peak of 25±3 mmHg) and tachycardic (peak of 60±25 bpm) responses. LOS injected into the 4thV had no effect on MAP, but it induced bradycardia (peak of -35±15 bpm). KCl (200 nmol/2 μl) injected into the 3rdV or into the 4thV had no effect on either MAP or HR compared to 0.9% saline injection. The results indicate that LOS injected into the third ventricle acts on forebrain structures to induce its pressor and tachycardic effects and that bradycardia, likely dependent on hindbrain structures, is obtained when LOS is injected into the fourth ventricle.
Keywords: angiotensin; blood pressure; cerebral ventricles; heart rate; losartan; angiotensin antagonist; animal experiment; bradycardia; cardiovascular effect; controlled study; hemodynamics; intracerebroventricular drug administration; male; nonhuman; pressor response; rat; tachycardia; Analysis of Variance; Animal; Biphenyl Compounds; Blood Pressure; Heart Rate; Imidazoles; Injections, Intraventricular; Losartan; Male; Rats; Rats, Sprague-Dawley; Support, Non-U.S. Gov't; Tetrazoles